Living a stressful life with joy - "Goel, Dewakar" (New Delhi, 2010)
Islam does not merely have a set of religious injunctions, but also a perfect system, based on do`s and don`ts, which determine a safe and secure system of life. As far as economics is concerned, Islam strongly suggests interest-free banking. Decentralization of money is another important principle. Money earned through honest and fair means has a number of benefits, which can only be experienced. As for modes of earning, Islam prefers business and agriculture. Basically, Islam believes in hard work, dedication and honesty. Islam also enjoins upon its followers to divide their earnings and earmark a certain portion for the needy and poor. Since Islam aims at benefiting humans on all counts, Allah has given such a perfect system of life, which transcends the limits of time. After the demise of the Prophet (Pbuh), pious Caliphs organized the public treasury, called Bail-ul-Maii which was aimed at helping the needy and the poor Muslims. If we talk of the division of money or property, as a part of inheritance, Islam has given a very clear-cut formula. A boy gets double the share of a girl. This formula can be applied everywhere, be it the division of property, money or any other capital. Similarly, there is another concept of loaning without charging any interest. Those who are capable are commanded to help those who are in need, and when they return the lent money, not to charge any extra amount. This would benefit the giver, as he would be divinely blessed for ever. In short, Islamic economy is based on overall benevolence of mankind. There are various works, which have been prepared on the economic aspects of Islam, but they all deal with general concepts and not the specific aspects of the subject. Given this situation, the present modest work has been prepared. Hopefully, it would be accorded a warm welcome by all people related to this field.
Keywords: Stress